GHI: A decade of promoting action against hunger and malnutrition - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
2016 will mark 11 years of the Global Hunger Index (GHI). For more than a decade, the GHI has contributed to increasing accountability to improving hunger and malnutrition at the global, regional, and national levels. Moreover, the annual GHI reports have been providing thought-provoking information on hunger and undernutrition that call all stakeholders to continued action against these complex challenges. Many country governments draw from the GHI to bring attention to the prevalence of hunger and malnutrition and, more importantly, to compel policymakers, sector leaders, and other stakeholders to work together in these issues.